Leadership in construction: a scientometric review - Peng, Wang; Haron, Nuzul Azam; Alias, Aidi Hizami; Law, Teik Hua (Multidisciplinary Digital Publishing Institute, 2022)
Leadership plays an increasingly important role in construction projects, and numerous research studies have been conducted. This study aims to identify the structure evolution development trends of this knowledge domain using visualisation analysis with CiteSpace. A total of 1789 peer-reviewed articles are collected from Scopus and the WoS core collection database to conduct a scientometric analysis. The results indicate that the US dominates this field and that institutions from Australia have made greater contributions. However, international cooperation in this area is not active. A total of eight co-citation clusters were identified, and the research of leadership in construction primarily focused on the topics of transactional leadership, safety leadership, team performance, leadership interaction processes and actual leader behaviour. The keywords co-occurrence evolution analysis was also conducted to provide a holistic knowledge map. Based on the development of this field and its current status, we propose trends and innovative research areas for future research. The findings in this research would help scholars to understand the structure and future trends of this field. Meanwhile, the research results would provide a reference for construction enterprises to formulate project manager competency criteria.